Location of transformers during the extension of an electricity distribution network - AKAR, ONUR; TERZİ, ÜMİT KEMALETTİN (My University, 2022)
The electricity network of a country is in continuous development, including the distribution transformers that provide power within a city. Efficient electricity networks depend on the good implementation of the principles of network planning and development. Moreover, technology development and the increasing standard of living are creating greater electricity demand. Besides, housing developments alter the need for electricity in an urban area and will require changes to control load density, adjustment of the voltage on distribution lines, installation of new lines and substations, and restructuring of existing ones. This study develops new mathematical and geometric methods that can be applied to all Low Voltage distribution networks to investigate load distribution, the effects of change and, provide a tool for distribution network planning. The analysis included the electrical power values to the new transformer, the shortest distribution routes between the transformers, and the costs, and provided optimum locations for new transformers. In this way, distribution network planning has been approached with a new method.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Engineering and Technology; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Elektrik ve Elektronik Mühendisliği; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Electrical and Electronic Engineering; Engineering (miscellaneous); Physical Sciences; Substation determination; Coverage-area; Distribution network planning; Optimization; Distribution transformer; Load density; SUBSTATION; SYSTEM; MODEL